Insights from organic farmers in Punjab: A survey on practices, challenges and market access - S S WALIA; A S SIDHU; C S AULAKH; NARINDER KUMAR (The Indian Journal of Agricultural Sciences)
The present study was carried out during 2020–21 to 2023–24 at Punjab Agricultural University, Ludhiana, Punjab under the All-India Network Programme on Organic Farming (AI-NPOF) to conduct a geo-tagged characterization of organic and natural farmers among 98 farmers in Punjab (Faridkot, Ludhiana, Malerkotla and Barnala). The survey was based on the questionnaire provided by the AI-NPOF lead centre, ICAR-Indian Institute of Farming Systems Research (IIFSR), Modipuram, Meerut, Uttar Pradesh, to elucidate the management practices, yield, profit and soil- health benefits of organic farming. Fifty percent of the farmers were small and marginal and rest 50% were semi- medium and medium and the 80% of the farms were organic certified. Major crops grown organically were wheat, basmati rice and vegetables (garlic, onion, peas, okra, bottle guard, pumpkin, palak, carrot, radish etc.), gobhi sarson, gram, turmeric, maize and fodder crops. Organic farmers utilized farmyard manure, green manuring, vermicompost, and liquid organic manures like vermiwash, beejamrit, jeevamrit and ghanjeevamrit for soil health. Botanicals such as neem biopesticides, agniastra, brahmastra, sour buttermilk and tricho-cards were employed for pest and disease management. Farm waste was recycled by composting and vermicomposting for nutrient management. The major constraint faced by farmers in adoption of organic farming was labour intensive operations (36%) and lack of marketing facilities (31.5%). Other constraints included were weed control (14.3%) and reduced yield (9%). These findings highlight the need for labour-saving technologies, better market infrastructure and targeted research on weed management and soil fertility to enhance organic farming adoption and sustainability, ensuring long-term economic and environmental benefits for farmers.